2008
DOI: 10.1016/j.chom.2008.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella AvrA Coordinates Suppression of Host Immune and Apoptotic Defenses via JNK Pathway Blockade

Abstract: Salmonellae are bacterial pathogens that have evolved sophisticated strategies to evade host immune defenses. These strategies include the secretion of effector proteins into mammalian cells so as to subvert innate immune and apoptotic signaling pathways, thereby allowing Salmonella to avoid elimination. Here, we show that the secreted Salmonella typhimurium effector protein AvrA possesses acetyltransferase activity toward specific mitogen-activated protein kinase kinases (MAPKKs) and potently inhibits c-Jun N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
250
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(259 citation statements)
references
References 45 publications
8
250
1
Order By: Relevance
“…HopZ1a may have originally evolved to acetylate an immunerelated kinase to suppress plant immunity similar to the function of other members of the YopJ superfamily (11,12,30,39,40). We speculate that HopZ1a-induced virulence involves manipulation of a ZED1-related kinase, in addition to other known virulence targets like microtubules (18).…”
Section: Discussionmentioning
confidence: 99%
“…HopZ1a may have originally evolved to acetylate an immunerelated kinase to suppress plant immunity similar to the function of other members of the YopJ superfamily (11,12,30,39,40). We speculate that HopZ1a-induced virulence involves manipulation of a ZED1-related kinase, in addition to other known virulence targets like microtubules (18).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggested that AvrA inhibits the NF-κB pathway [175]. Inhibition of c-Jun N-terminal kinase (JNK) and NF-κB signaling pathways were observed in transgenic Drosophila and murine models leading to suppression of innate immunity, inflammation, and apoptosis during natural infection [176]. Recently, DNA microarray analysis of mouse colon mucosa infected with wild-type or AvrA − Salmonella suggested that several pathways, including mTOR, NF-κB, platelet-derived growth factors, vascular endothelial growth factor, oxidative phosphorylation, and MAPK signaling, are specifically regulated by AvrA in vivo [127].…”
Section: An Alphabetical Guide Tomentioning
confidence: 99%
“…This, in turn, stabilizes β-catenin, a downstream target of Wnt. Proposed targets for the acetyltransferase activity of AvrA are MAPK kinase 4 (MKK4) in a Drosophila model, leading to inhibition of JNK [176] and p53. p53 acetylation is increased by AvrA in vitro and in an in vivo mouse model.…”
Section: An Alphabetical Guide Tomentioning
confidence: 99%
“…SptP GAP and tyrosine phosphatase activities play critical roles in reversing MAPK activation while AvrA acetyltransferase activity towards MAPK kinases inhibits Jnk activation (Jones et al, 2008;Lin et al, 2003;Murli et al, 2001). Moreover, SpvC has been shown to directly inhibit Erk, Jnk and p38 MAPKs via its phosphothreonine lyase activity (Li et al, 2007;Mazurkiewicz et al, 2008).…”
Section: Surviving Intracellularlymentioning
confidence: 99%